The Relationship of Total Output to Man-Hour Output: Reply - Oliver, Henry M. (Quarterly Journal of Economics, 1945)
Journal Article The Relationship of Total Output to Man-Hour Output: Reply Get access Henry M. Oliver, Jr. Henry M. Oliver, Jr. Lt., USNR Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 59, Issue 4, August 1945, Pages 640–641, https://doi.org/10.2307/1883301 Published: 01 August 1945